Cuticular Hydrocarbon Profile Analyses Help Clarify the Species Identity of Dry-Mounted Cuckoo Wasps (Hymenoptera: Chrysididae), Including Type Material, and Reveal Evidence for a Cryptic Species. Issue 1 (20th February 2021) - Soon, Villu; Castillo-Cajas, Ruth F; Johansson, Niklas; Paukkunen, Juho; Rosa, Paolo; Ødegaard, Frode; Schmitt, Thomas; Niehuis, Oliver
Abstract: Cuckoo wasps of the Chrysis ignita species group are difficult to identify at the species level, and the taxonomic status of various taxa has consequently been controversial. COI barcoding has helped clarify some of the taxonomic problems in this group, but also revealed cryptic diversity at the genetic level that remained difficult to interpret taxonomically. Here we show that analysis of cuticular hydrocarbons (CHCs) clarifies the taxonomic status of cuckoo wasp samples with distinct COI haplotypes. The advantages of studying CHCs in insects for taxonomic purposes reside on the fact that CHC profiles evolve quickly and that all proteins required for CHC biosynthesis are encoded by nuclear genes. Using Chrysis pseudobrevitarsis as an example, we show that COI barcoding in combination with analysis of CHCs extracted from freshly collected and from dry-mounted museum specimens (including the lectotype of C. pseudobrevitarsis ) provides clear evidence for a separate taxon among samples which were previously considered to be conspecific with C. pseudobrevitarsis . We describe this taxon as Chrysis parabrevitarsis n. sp. and present characters for distinguishing it chemically, genetically, and morphologically (females only) from C. pseudobrevitarsis . CHC profile comparison suggests females of C. pseudobrevitarsis may chemically mimic females of the vespid wasp Euodynerus notatus . Our study demonstrates the value of CHC analyses for supporting taxonomic inferences based on COI barcodes. It additionally underlines the value of dry-mounted collection specimens for chemical analyses and the potential of CHCs for inferring the identity of museum specimens, including type material, in a morphologically noninvasive manner.